2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6883802
|View full text |Cite
|
Sign up to set email alerts
|

Allowing applications to evolve with the Internet: The case for Internet Resource Descriptors

Abstract: Today's socket API requires an application to bind a socket to a network address before it can use the socket to communicate. Early bindings of names to addresses create significant bottlenecks, reliability problems, and force applications to manage complex lower-layer issues. Many approaches have been introduced to address this problem; however, all prior proposals introduce additional identifiers, modify applications, or require additional protocols in the protocol stack. In contrast, we propose a generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We have provided simple proofs-of-concept implementations of the concept of hidden identifiers [1], [2]. This paper extends this prior work into a robust, three-part network architecture we call HIDRA (Hidden Identifiers for Demultiplexing and Resolution Architecture).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…We have provided simple proofs-of-concept implementations of the concept of hidden identifiers [1], [2]. This paper extends this prior work into a robust, three-part network architecture we call HIDRA (Hidden Identifiers for Demultiplexing and Resolution Architecture).…”
Section: Introductionmentioning
confidence: 82%
“…As a result, this requirement ensures that the identifiers used by the higher layer are scoped correctly, and can therefore be resolved unambiguously by the higher layer. 1 In this context, we use "name" and "address" interchangeably, since as [3] points out, an "address" is just the "name" of a lower-level entity.…”
Section: Hidden and Open Identifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, part of the justification of recent ICN architectures is the argument that using addresses is inherently limiting in supporting the mobility of services or content. However, as we have argued recently [45], [46], [47], the limitations of prior proposals stem from the assumption that the identifiers used in the communication protocols operating in the data plane must be the same as the identifiers used within the protocol stack of a host or a router to pass information across layers of the stack. We have demonstrated that this does not have to be the case and that indirection within the protocol stack can be done efficiently to allow names and addresses used in communication protocols to differ from the identifiers used inside hosts and router to refer to resources, connections, or remote processes.…”
Section: E Limitations Of Prior Solutionsmentioning
confidence: 99%
“…First, our prior work on "hidden identifiers" in the protocol stack [45], [46], [47] demonstrates that hosts and routers can denote resources, connections and remote processes with identifiers that need not be the same as those used as part of communication protocols. Second, updating the mappings from names to addresses need not be done solely through a common directory service, and indeed communicating hosts or routers can update one another directly if done properly.…”
Section: E Limitations Of Prior Solutionsmentioning
confidence: 99%